Comparing co-production approaches to dynamic risk assessments in a forensic intellectual disability population: outcomes of a clinical pilot. Issue 1 (4th January 2021) - Morris, Deborah J.; Webb, Elanor L.; Stewart, Inga; Galsworthy, Jordan; Wallang, Paul
Abstract : Purpose: A co-produced clinical practice that aims to improve outcomes through a partnership with service users is becoming increasingly important in intellectual disability (ID) services, yet these approaches are under-evaluated in forensic settings. This study aims to explore and compare the feasibility of two approaches to co-production in the completion of dynamic risk assessments and management plans in a secure setting. Design/methodology/approach: A convenience sample of adults admitted to a secure specialist forensic ID service ( N = 54) completed the short dynamic risk scale (SDRS) and drafted risk management plans under one of two conditions. In the first condition, participants rated the SDRS and risk management plan first, separately from the multidisciplinary team (MDT). In the second condition, participants and MDTs rated the SDRS and risk management plan together. Findings: In total, 35 (65%) participants rated their risk assessments and 25 (47%) completed their risk management plans. Participants who rated their risk assessments separately from the MDT were significantly more likely to complete the SDRS ( p = 0.025) and draft their risk management plans ( p = 0.003). When rated separately, MDT scorers recorded significantly higher total SDRS scores compared to participants ( p = 0.009). A series of Mann-Whitney U tests revealed significant differences between MDT and participant ratings on questions that required greater skills in abstraction and social reasoning, as well as sexual behaviour and self-harm. Originality/value: Detained participants with an ID will engage in their dynamic risk assessment and management plan processes. The study demonstrates the impact of different co-production methodologies on engagement and highlights areas for future research pertaining to co-production.